KOPI-SENJA DAN INDIE: ANALISIS REPRESENTASI LAGU ‘TAK PERLU ADA SENJA’ DAN ‘KOPI, SENJA, DAN LOGIKA’ - Restiawan Permana; Yusmawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Song lyrics are an example of how music is a cultural tool that is used in society to shape social reality. Because there was no power relations from market demand during the industrialization of independent music, it became a counterculture. Indie music is a new lifestyle trend, especially for coffee lovers, because it frequently features songs with poetic lyrics about savoring the sunset as well as resistance. Fans of independent music cannot separate the three elements of dusk, coffee, and indie music. This study aims to examine how coffee-speech is portrayed in two songs with twilight themes. The formulation of the problem in this study is how the lyrics of the song 'Tak Perlu Ada Senja' sung by Suara Kayu ft. Fiersa Besari and the song 'Kopi, Senja, dan Logika' sung by the band Nosstress represent kopi-senja as a new term for indie music fans in Indonesia ?”. This research is a qualitative research through a textual/literary approach using Ferdinand de Saussure's semiotic analysis method. The author divides the song's text into two meanings, the signifier and the signified, using Ferdinand de Saussure's semiotic analysis. In conclusion, coffee and dusk go hand in hand with indie music. It turns out that coffee is a popular beverage among people who do more than just hang out in coffee shops. However, coffee has a positive energy that might inspire.